PEMBERDAYAAN PEREMPUAN DALAM MEMBANGUN BUDAYA ANTI KORUPSI - Muhandis Azzuhri (UIN K.H. Abdurrahman Wahid Pekalongan, 2011)
The stereotype that women are categorized as the second human in all aspects of life it was time to be removed. The role of women is now considered to be very strategic in determining all legal policy, politics, social life of the nation. Corruption as a result of manipulation of the public on the budget authority in a system regarded as a chronic disease that must be healed until the roots. This is where the role of women is very significant that the quality of education needs to empower them so that they can work together to build a culture of anti-corruption